SANKSI HUKUM TERHADAP PELAKU USAHA YANG TIDAK MEMBAYAR UPAH KARYAWAN SESUAI DENGAN PERATURAN HUKUM DI INDONESIA - Daniel Satria Setyawan Putra; Suryanto; Pebri Ramuda Pandiangan; Mohamad Fahmi Fiddin; Adithia Osea; Luthfi El Hakim Saragih (Collegium Studiosum Journal, 2025)
This study aims to analyze the legal sanctions imposed on businesses that fail to pay employee wages in accordance with Indonesian laws and regulations and to assess the effectiveness of their enforcement. Wages are a basic right of every worker, guaranteed by Law Number 13 of 2003 concerning Manpower, as amended by Law Number 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation into Law. Employers' obligation to pay wages in accordance with applicable regulations embodies the principles of justice, humanity, and legal certainty in industrial relations. The research method used is normative juridical, with a statutory and conceptual approach. The data used are sourced from primary, secondary, and tertiary legal materials, analyzed qualitatively. The results indicate that businesses that fail to pay employee wages in accordance with regulations may be subject to administrative sanctions, such as written warnings, restrictions on business activities, temporary suspension, and even revocation of business licenses. Furthermore, there are criminal sanctions as stipulated in Article 185 of the Manpower Law, which carry a maximum imprisonment of four years and/or a maximum fine of four hundred million rupiah. However, in practice, enforcement of these legal sanctions remains suboptimal due to weak labor oversight and low legal awareness among business actors. This study concludes that increased effectiveness of labor oversight and stricter law enforcement are needed to ensure the protection of workers' rights to decent wages in accordance with the principles of social justice in Indonesia.